Understanding Machine Learning for Friction Stir Welding Technology - Mishra, Akshansh (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2021)
Machine learning process drastically decreases the time it takes to develop stronger, lighter materials. This is important to the aerospace, automotive and manufacturing sectors. Machine Learning techniques like Artificial Neural Networks and Image processing are used in Friction Stir Welding process for the optimization of mechanical properties like Ultimate Tensile Strength, Fracture Strength and elongation % and microstructure properties like grain size and understanding defects formation. In the recent paper, application of Machine Learning technique in Friction Stir Welding technology will be discussed. How to cite this article: Akshansh A. Understanding Machine Learning for Friction Stir Welding Technology. J Adv Res Appl Arti Intel Neural Netw 2020; 4(1): 33-41